Legal Study On The Perpetrators Of Extortion (Pungli) In The Aek Sijorni Tourist Spot In The Perspective Of Law No. 31 Of 1999 Jo. Law No. 20 Of 2001 Concerning The Eradication Of Criminal Acts Of Corruption - Baginda Pane; Zainal Abidin Pakpahan; Toni Toni (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The purpose of this study is to discuss extortion. Extortion is an abbreviation of illegal levies, which is the act of asking for something without a clear and official legal basis. Extortion is a form of extraordinary crime and is categorized as a criminal act of corruption regulated by law. Extortion often occurs due to abuse of office authority by an individual or group of individuals from a particular agency. Extortion activities often disturb the community. It even becomes a threat because the perpetrators often use threats or physical violence to achieve their goals. The type of research used is normative research, with an approach method through legislation. Results of the discussion: Extortion is an unlawful act that has been regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption concerning the eradication of criminal acts of corruption. Criminal sanctions for perpetrators of extortion are imposed under Article 368 of the Criminal Code which states that: